Activating cellulose via its reversible reaction with CO2 in the presence of 1, 8-diazabicyclo[5.4.0]undec-7-ene for the efficient synthesis of cellulose acetate1. Issue 5 (12th May 2015) - Yang, Yunlong; Song, Longchu; Peng, Chang; Liu, Enhui; Xie, Haibo
<x xml:space="preserve">Abstract</x> Reversible reaction of cellulose with CO2 in DMSO/DBU results in a derivative dissolution of cellulose, which can be applied for the efficient acetylation of cellulose to afford cellulose acetates with degrees of substitution from 1.78–2.89.